The Effect of Gadget Toward Early Childhood Speaking Ability - Nirwana, Nirwana; Mappapoleonro, A Musda; Chairunnisa, Chairunnisa (Indonesian Journal of Early Childhood Education Studies, 2018)
This study examines the effect of gadget toward early childhood speaking ability especially those in the age range of 3-4 years. The 3-4 years old children generally have enthusiasm in speaking, their curiosity tend to be greater, such as telling something that happened around them to the closest person. However, the presence of gadget in this digital era has negative influences on their speaking ability. The majority of children in Indonesia spend time playing gadget. The study seeks to explain the use of gadget toward early childhood speaking ability. The methodological approach taken in this study is literature review by connecting this study with existing literature and previous researches which have limited investigations. The result obtained in this study indicates that the use of gadget can delay the children speaking ability, especially children aged 3-4 years.